2016
DOI: 10.1016/j.paid.2016.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Optimism and attributional style impact on the relationship between general insecurity and mental health

Abstract: The current research examined the impact of general insecurity beyond specific domains on mental health, and optimism as the proposed mechanism explaining the aforementioned relationship. We also tested external attribution as a possible moderator. We collected data (N = 219) in two waves. Results showed that general insecurity is negatively associated with mental health, and this relationship was mediated by optimism. Moreover, the external attribution buffered the aforementioned impacts, playing a role of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 47 publications
2
18
0
1
Order By: Relevance
“…Moreover, the clinical group shows a "pessimistic" attribution bias as an important differential trait comparing to controls, with a great effect size. The finding agrees with some studies linking optimism to better mental health levels (Yuan & Wang, 2016). Within the clinical group, "pessimism" predicted more than 40% of the variance in depressive symptoms according to predictions of the Theory of Hopelessness of Depression (Haeffel et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the clinical group shows a "pessimistic" attribution bias as an important differential trait comparing to controls, with a great effect size. The finding agrees with some studies linking optimism to better mental health levels (Yuan & Wang, 2016). Within the clinical group, "pessimism" predicted more than 40% of the variance in depressive symptoms according to predictions of the Theory of Hopelessness of Depression (Haeffel et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…In a study of Yuan and Wang (2016), they examined the relationship between general insecurity and general mental health, in which optimism acted as a mediator and attribution style acted as a moderator. It is found that general insecurity can be harmful to general mental health through damaging optimism, but using external attribution strategy can help to reduce the consuming effect of insecurity and thus maintains optimism and mental health.…”
Section: How Does Job Insecurity Affects Mental Healthmentioning
confidence: 99%
“…Studies by Peterson and several meta-analyses (Peterson, Villanova, & Raps, 1985;Sweeney et al, 1986;Hu, Zhang, & Yang, 2015) confirmed that a pessimistic attributional style for negative life outcomes is a reliable predictor of depression. Other studies revealed that a pessimistic attributional style for negative events is associated with anxiety (Lynd-Stevenson & Rigano, 1996;Ralph & Mineka, 1998), hostility (Boman, Smith, & Curtis, 2003), and neuroticism (Cheng & Furnham, 2001), as well as health issues (Peterson & Seligman, 1987;Yuan & Wang, 2016), and health complaints (Reilley, Geers, Lindsay, Deronde, & Dember, 2005). Studies of OAS-Positive have long been neglected, and Peterson would later conclude that this neglect of positive events was a regrettable mistake .…”
Section: Optimistic Attributional Style For Negative and Positive Eventsmentioning
confidence: 99%